A Growth-Friendly Path for Building Fiscal Buffers in the Caucuses and Central Asia - Gemayel, Edward (Departmental Papers; Departmental Paper ;, 2018)
Since 2014, large and persistent external shocks have hit the CCA region, particularly a slump in global commodity prices and slower growth in its key economic partners. Fiscal accommodation, along with currency adjustment, has helped the CCA mitigate the impact of the external shocks. However, amid weakening revenues, increased public spending has widened budget deficits, weakened external balances, and increased public debts. Fiscal policy and strengthening fiscal frameworks must play a central role in helping build buffers and ensuring debt sustainability while supporting growth. This requires (1) tightening fiscal policies to reduce deficits to help restore external balance and fiscal sustainability, (2) strengthening tax systems and tax collection and tilting expenditure toward a more productive and growth-enhancing composition, and (3) implementing public financial management reforms and strengthening fiscal institutions, including through fiscal rules.